2019
DOI: 10.1038/s41598-019-54035-y
|View full text |Cite
|
Sign up to set email alerts
|

Degree of conversion of experimental resin composites containing bioactive glass 45S5: the effect of post-cure heating

Abstract: Resin composites containing reinforcing inert glass fillers combined with bioactive glass (BG) can aid in the prevention of secondary caries, which is a major cause of failure of contemporary composite restorations. A series of previous studies on experimental resin composites filled with BG 45S5 has demonstrated that methacrylate resin polymerization can be impaired by the addition of unsilanized BG, leading to lower degrees of conversion (DC). In order to distinguish whether the polymerization inhibition is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
58
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 43 publications
6
58
2
1
Order By: Relevance
“…Previous studies showed that the DC of resin composites could be impaired by the addition of BG 45S5 [22][23][24]. This phenomenon was confirmed in the present study for the composite series functionalized with BG 45S5, which showed a dose-dependent DC decline.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies showed that the DC of resin composites could be impaired by the addition of BG 45S5 [22][23][24]. This phenomenon was confirmed in the present study for the composite series functionalized with BG 45S5, which showed a dose-dependent DC decline.…”
Section: Discussionsupporting
confidence: 90%
“…The degree of conversion (DC) represents a fundamental parameter governing mechanical properties and biocompatibility of polymer-based materials [18][19][20][21]. Previous studies indicated that BG 45S5 can impair the DC of experimental resin composites [22][23][24]. Since the present study is the first to investigate a particular novel BG composition, the possibility of it exerting a negative effect on DC was evaluated.…”
Section: Introductionmentioning
confidence: 94%
“…This indicates that the resin mobility was not hindered by the high surface area of nano-sized BG any more than the 30 times lower surface area of micro-sized particles. A dose-dependent potential of BG 45S5 for diminishing the DC of experimental composites has been observed in a previous study [27]. The present study demonstrated that downsizing the BG fillers exerted no inhibitory effect on resin polymerization.…”
Section: Discussionsupporting
confidence: 85%
“…The usual trade-off between bioactivity and mechanical properties can be fine-tuned by varying relative amounts of reinforcing and reactive fillers [25]. Resin matrix composition can be adjusted to optimize hydrophilicity [26] and degree of conversion (DC) [27]. Additionally, BG fillers can be downsized from micrometric to nanometric scale [21,[28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The degree of conversion is an essential material characteristic of dental resin composites, affecting both physical and mechanical as well as biological polymer properties [34][35][36][37][38][39][40][41]. In the current study, the added micro-fillers did not affect the degree of conversion at the specimens' top surface, irrespective of the bulk-fill composite used.…”
Section: Discussionmentioning
confidence: 48%